To seek program accreditation, innovation, or both? Examining the interdependencies in high-reliability health care organizations - Tim Brand; Eva Goetjes; Katharina Blankart (Schmalenbach Journal of Business Research (SBUR), 2023)
In dynamic markets, organizations have to be ambidextrous to adapt to constant change. Simultaneously, organizations are increasingly required to adopt quality management accreditation. Standardization through accreditation bares the risk of limiting an organization's dynamic capabilities. In this study, we aim to evaluate the determinants of organizational decision-making to seek accreditation and pursue innovation activities, whether accreditation and innovation activities help organizations reach their strategic goals, and if accreditation affects the ability to achieve ambidexterity. We explore these relationships in high-reliability health care organizations. We conducted semi-structured interviews with 11 physicians and 14 quality managers in hospitals that provide specialized cancer care in Germany. In an inductive grounded theory approach, we develop a conceptual model of the relationship between accreditation and innovation activities. We find that hospitals engaged in both activities to achieve quality and financial goals. For smaller hospitals, accreditation was a necessary condition to be able to compete in market environments. Regardless of competition, smaller hospitals benefitted from a positive effect of accreditation on incremental process and product innovation. For larger hospitals, obtaining accreditation was a necessary condition to acquire additional funding, but the influence on innovation activities was limited because these were already being pursued with high intensity. Ideally, program accreditation and innovation activities can be aligned to achieve superior quality and financial performance through organizational ambidexterity. Organizational decision-makers must align both activities while taking account of costs and benefits. Policy makers can support access to high quality care by setting incentives to acquire accreditation.
Keywords: 650; Grounded theory; Accreditation; Certification; Innovation; Hospitals; Cancer